2021
DOI: 10.56027/joasd.spiss092021
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Medicago sativa varieties tolerance to Phoma medicaginis infection.

Abstract: Due to its very important agronomic value and nutritional quality, Medicago sativa L. is considered as the queen of fodder and the first cultivated forage crop in the world. In field conditions, M. sativa is exposed to several biotic and/or abiotic constraints that affect its quality. In this regard, research is still underway to improve M. sativa resistance to many biotic stresses and, in this context, we analyzed the responses of a core collection of 10 varieties of M. sativa to Phoma medicaginis infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Badri et al (2023) tested the effect of P. medicaginis on the variation in agronomic traits of different Medicago species, reporting that most of the variation in the measured parameters was explained by the infection treatment. Zaidi et al (2021) demonstrated that the number of healthy leaves (recorded among the infection parameters of alfalfa genotypes) varied significantly among the genotypes infected by P. medicaginis, which is consistent with the current observations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Badri et al (2023) tested the effect of P. medicaginis on the variation in agronomic traits of different Medicago species, reporting that most of the variation in the measured parameters was explained by the infection treatment. Zaidi et al (2021) demonstrated that the number of healthy leaves (recorded among the infection parameters of alfalfa genotypes) varied significantly among the genotypes infected by P. medicaginis, which is consistent with the current observations.…”
Section: Discussionsupporting
confidence: 92%
“…After 2 months of cultivation, plants at the flowering bud stage were subjected to a saline treatment of 150 mM NaCl (for 21 days) until the appearance of symptoms related to saline stress. At this stage, they were infected with the strain Pm8 of Phoma medicaginis (5*10 6 conidies µL -1 ) as described by Zaidi et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, analysis of the responses of 10 varieties of M. sativa to infection by P. medicaginis revealed that the studied varieties are classified into three large groups [32]. The first group is formed by Gabès2353, the second group is constituted of the Californian and El Hamma varieties, and the third group is composed of the remaining seven varieties.…”
Section: Adaptation To Abiotic and Biotic Constraintsmentioning
confidence: 99%
“…Finally, Medicago species showed a high level of variability in responses to abiotic and biotic stresses. Diversity within and among populations has been noted for water deficit [24], salinity [25][26][27], nutritional deficiencies [28], and resistance to pathogens [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%